Rehabilitation success and related costs following stroke in a regional hospital: a retrospective analysis based on the Australian National Subacute and Non-Acute Patient (AN-SNAP) classification - Fan He; George Mnatzaganian; Michael Njovu; David Rutherford; Tara Alexander; Irene Blackberry (BMC Health Services Research)
Abstract Background Evidence is limited on the factors influencing successful stroke rehabilitation in regional contexts. Additionally, the relationship between rehabilitation costs following acute stroke, based on Australian National Subacute and Non-Acute Patient (AN-SNAP) casemix classification, and rehabilitation success remains unclear. Objective This retrospective cohort study investigated the factors contributing to improved functional outcomes following stroke rehabilitation in an Australian regional hospital, also evaluating the respective average daily and total payments. Methods Stroke patients’ admission records, during 2010–2020, were linked with rehabilitation registry data. Rehabilitation success was defined as relative functional gain (RFG) ≥ 0.5 and Functional Independence Measure (FIM) efficiency ≥ 1. Multivariate mixed effects logistical regressions modelled the sociodemographic and medical (i.e., comorbidities and stroke type) predictors of rehabilitation success, while logarithms of average daily and total rehabilitation payments were modelled using robust regressions. Results Of 582 included patients, 315 (54.1%) achieved RFG ≥ 0.5 and 258 (52.2%) achieved FIM efficiency ≥ 1. A longer delay in starting rehabilitation was associated with a lower likelihood of achieving RFG success [Odds Ratio (OR): 0.85, 95% confidence interval (CI): 0.78–0.93, P < 0.001] and FIM efficiency success (OR: 0.89, 95% CI: 0.82–0.97, P = 0.010). A higher FIM score at admission was associated with decreased odds of FIM efficiency success (OR: 0.35, 95% CI: 0.20–0.60, P < 0.001). The average daily and total rehabilitation payments for inpatients were $AU1,255 (median) [interquartile range (IQR): 1,040, 1,771] and $AU28,363 (median) (IQR: 18,822, 41,815), respectively. FIM efficiency success was positively associated with the average daily payment (Beta: 0.25, 95% CI: 0.20–0.30, P < 0.001), but negatively correlated with the total payment (Beta: -0.18, 95% CI: -0.24–0.13, P < 0.001). No significant associations were found between RFG success and these payments. Conclusion This study identifies key factors affecting stroke rehabilitation outcomes in a regional Australian setting. Delays in starting rehabilitation were linked to lower success rates, underscoring the importance of timely intervention. While higher average daily costs were associated with better FIM efficiency, total costs did not correlate with relative functional gains. These findings may inform rehabilitation practices and may influence future funding strategies for rehabilitation services.